Analisis Tindak Tutur Lokusi pada Daftar Putar Video Pembelajaran Bahasa Indonesia dalam Kanal Revi Nurmeyani - Benedikta Agusta Kandam; Winna Widyadhana; Mei Ismiyanti; Ikhwan Abdul Aziz; Rizqi Ardiansyah; Rossa Farhana Ridho Susanti; Asep Purwo Yudi Utomo (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Pragmatics is a branch of linguistics that studies the meaning of speech. One of the pragmatic materials is analyzed in this research, namely elocutionary speech acts. Locutionary speech acts themselves are speech acts with the intention of completing something. The thing that underlies this research is the researcher's curiosity about the application of illocutionary speech acts in a speech. This research aims to determine and describe the form of illocutionary speech acts in a news text learning video on Revi Nurmeyani's YouTube channel. The approach used to research this research is to use a theoretical and methodological approach, the theoretical approach used is a pragmatic approach while the methodological approach used is a qualitative descriptive approach. The data source used is speech in Revi Nurmeyani's news text learning video. Data collection was carried out using the matching and sharing method. The results of the analysis are presented using informal methods. The research results found locutionary speech acts in the parts of inviting, informing, explaining, asking and reminding with a total of 76 data taken from the data source, namely Revi Nurmeyani's YouTube channel, discussing news text material. This research can be used as reference material for understanding locutionary speech act material in pragmatics, besides that it can also be used as supporting material or examples for further research related to pragmatic material, especially regarding locutionary speech acts.